First Radial Velocity Results From the MINiature Exoplanet Radial Velocity Array (MINERVA). (18th September 2019) - Wilson, Maurice L.; Eastman, Jason D.; Cornachione, Matthew A.; Wang, Sharon X.; Johnson, Samson A.; Sliski, David H.; Schap III, William J.; Morton, Timothy D.; Johnson, John Asher; McCrady, Nate; Wright, Jason T.; Wittenmyer, Robert A.; et al.
Abstract: The MINiature Exoplanet Radial Velocity Array (MINERVA) is a dedicated observatory of four 0.7 m robotic telescopes fiber-fed to a KiwiSpec spectrograph. The MINERVA mission is to discover super-Earths in the habitable zones of nearby stars. This can be accomplished with MINERVA's unique combination of high precision and high cadence over long time periods. In this work, we detail changes to the MINERVA facility that have occurred since our previous paper. We then describe MINERVA's robotic control software, the process by which we perform 1D spectral extraction, and our forward modeling Doppler pipeline. In the process of improving our forward modeling procedure, we found that our spectrograph's intrinsic instrumental profile is stable for at least nine months. Because of that, we characterized our instrumental profile with a time-independent, cubic spline function based on the profile in the cross dispersion direction, with which we achieved a radial velocity precision similar to using a conventional "sum-of-Gaussians" instrumental profile: 1.8 m s −1 over 1.5 months on the RV standard star HD 122064. Therefore, we conclude that the instrumental profile need not be perfectly accurate as long as it is stable. In addition, we observed 51 Peg and our results are consistent with the literature, confirming our spectrograph and Doppler pipeline are producing accurate and precise radial velocities.